Cardiac Stress Test Trends Among U.S. Patients Under Age 65, 2005-2012 - Kini, Vinay (JAMA Cardiol, 2016)
IMPORTANCE: After a period of rapid growth, utilization of cardiac stress testing has recently decreased among Medicare beneficiaries and in a large integrated health system. However, it is not known whether declines in stress testing are universal, or are confined to certain populations. OBJECTIVE: To determine trends in stress test utilization rates among a large and diverse cohort of commercially insured patients. DESIGN: Serial cross-sectional study with time trends from 2005 to 2012. SETTING: Comprehensive administrative claims from a large national managed care company. PARTICIPANTS: All members of the national managed care company aged 25–64 years. MAIN OUTCOMES AND MEASURES: Age- and sex-adjusted rates of cardiac stress tests per calendar quarter. Linear trends in rates were determined using negative binomial regression models with procedure count as the dependent variable, calendar quarter as the key independent variable, and the size of the population as a logged offset term. RESULTS: We identified 2,085,591 stress tests performed among 32,921,838 unique persons, of whom 51% were women and 23% were non-white. There was a small (2%) increase in stress testing rates from 2005 to 2012 (3486 [95% CI: 3458 to 3514] versus 3552 [95% CI: 3522 to 3582] tests per 100,000 person-years; p for linear trend=0.01). Declines in nuclear single photon emission computed tomography (a 15% relative decrease; p=0.03) were offset by increases in the use of stress echocardiography (a 24% relative increase; p<.001), exercise electrocardiography (a 10% relative increase; p<.001), and other stress testing modalities (a 66% relative increase; p<.001). Rates of stress testing increased most significantly among members aged 25–34 years (a 70% relative increase; p<.001), but declined among members aged 55–64 (a 9% relative decrease; p<.001). CONCLUSIONS AND RELEVANCE: In contrast to declines in stress test use in some health care systems, we observed a small increase in stress test utilization among a nationally representative cohort of commercially insured patients. Our findings suggest that observed trends in stress test utilization may have been driven more strongly by unique characteristics of populations and health systems than national efforts to reduce overuse of testing.